1989
DOI: 10.1093/jaoac/72.4.632
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Survey of Selected Imported Spices and Associated Fecal Pellet Specimens

Abstract: A microbiological survey was performed on 4 selected imported spices: black peppercorns, white peppercorns, coriander, and fennel seed. Aerobic plate count values ranged from 104 to 107 colonyforming units (CFU)/g for black and white peppercorns and from 103 to 105 CFU/g for coriander and fennel seed. Combined results of the 3-tube most probable number procedure and the API 20E kit indicated the presence of Escherichia coli in 4 test samples of black peppercorns, 1 test sample of white peppercorns, and 1 test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In our masala spice mix samples, we observed a high prevalence of Enterobacter and Bacillus species with 16S rRNA gene sequencing, in agreement with previous spice investigations that measured total bacterial loads ranging from 10 2 to 10 7 CFU/gm, with a predominance of Enterobacter and Bacillus ( Pafumi, 1986 ; Satchell et al, 1989 ; Garcia et al, 2001 ; Sagoo et al, 2009 ; Sospedra et al, 2010 ). A survey of black peppercorns, white peppercorns, coriander, and fennel seeds identified Enterobacter cloacae as the most common Enterobacteriaceae member, which is consistent with our findings where proportional abundances of Enterobacter species ranged from 11 to 23% with additional abundances (7–13%) of unidentified Enterobacteriaceae that are likely Enterobacter species ( Satchell et al, 1989 ). The high bacterial diversity and number of unique species (19) we observed in masala spice was expected since the spice mixtures tested were comprised of as many as 17 different ingredients and most published studies were of individual spices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our masala spice mix samples, we observed a high prevalence of Enterobacter and Bacillus species with 16S rRNA gene sequencing, in agreement with previous spice investigations that measured total bacterial loads ranging from 10 2 to 10 7 CFU/gm, with a predominance of Enterobacter and Bacillus ( Pafumi, 1986 ; Satchell et al, 1989 ; Garcia et al, 2001 ; Sagoo et al, 2009 ; Sospedra et al, 2010 ). A survey of black peppercorns, white peppercorns, coriander, and fennel seeds identified Enterobacter cloacae as the most common Enterobacteriaceae member, which is consistent with our findings where proportional abundances of Enterobacter species ranged from 11 to 23% with additional abundances (7–13%) of unidentified Enterobacteriaceae that are likely Enterobacter species ( Satchell et al, 1989 ). The high bacterial diversity and number of unique species (19) we observed in masala spice was expected since the spice mixtures tested were comprised of as many as 17 different ingredients and most published studies were of individual spices.…”
Section: Discussionsupporting
confidence: 91%
“…Detection of adulteration or contamination, whether it be economically based or accidental exposure to a microbial pathogen, and the study of spoilage events are other areas where food microbiome research is growing. Historically, the assessment of quality and safety of food commodities, such as spices, was achieved using standard microbiological methods such as aerobic plate counts, and biochemical phenotypic typing assays to quantify and identify target bacteria ( Pafumi, 1986 ; Satchell et al, 1989 ; Garcia et al, 2001 ; Sagoo et al, 2009 ; Sospedra et al, 2010 ). In this study, we examined the bacterial microbiomes associated with several food commodities, to establish baseline data, which will be available publicly at the FDA MetagenomeTrakr bioproject at NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most spices and herbs contain a very high number of bacteria, thus contributing to the spoilage of food products (De Boer et al, 1985). The presence of Bacillus cereus, Clostridium perfringens, Escherichia coli, Staphylococcus aureus, Enterobacter cloacae, Klebsiella pneumoniae, as well as moulds of the genera Aspergillus, Penicillium, Rhizopus, Cladosporium, Cunninghamella and Trichoderma have been reported (Satchell et al, 1989;Garcia et al, 2001;Banerjee & Sarkar, 2003;Mandeel, 2005;Sagoo et al, 2009). Moreover, several spices, including turmeric, paprika, aniseed and pepper have been linked with salmonellosis outbreaks (Gustavsen & Breen, 1984;Lehmacher et al, 1995;Little et al, 2003;Koch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Under laboratory conditions, S. enteritidis and E. coli may persist in rodent fecal pellets for extended periods ranging up to 160 days (Badi et al, 1992;Kirchner et al, 1982;Ostrolenk et al, 1947;Welch et al, 1941); however, researchers who examined spices that were contaminated with rodent and bird feces found that the fecal contaminants from the various spices rarely contained Salmonella or E. coli. The researchers attributed their results to microbial "die off" as a result of the debilitating effects of natural drying of the feces (Satchell et al, 1989).…”
Section: Biological Hazards: Contributing Factorsmentioning
confidence: 99%